Global neurosurgery, Bangladesh and COVID-19 era - Robert Ahmed Khan; Moshiur Rahman; Amit Agrawal; Ezequiel Garcia-Ballestas; Luis Rafael Moscote-Salazar (Romanian Neurosurgery, 2020)
Background. COVID-19 has become an alarming pandemic for our earth. It has created panic not only in China but also in developing countries like Bangladesh. Bangladesh has adequate confinements to constrain the spread of the infection and in this circumstance, overall healthcare workers including neurosurgeons are confronting a ton of difficulties. The purpose of this paper is to depict the proficiency of Global neurosurgery in this COVID-19 time.